An Exploratory Study of Business Survival, Growth and Sustainability in The Food and Beverage Industry: A Malaysian Entrepreneur’s Perspective - Loo, Brendon Jiunn Wey (2013)
Entrepreneurs in the Food & Beverage (F&B) Industry today face many challenges including the ability to recognize and respond to customers’ needs and trends, market competition and volatility of raw material prices, amongst others. Restaurants and food outlets are also extremely susceptible to failure particularly during their first year due to severe competition. Reports indicate that nearly 25 percent of businesses fail within two years of setting up and an even more staggering 37 percent failed within five years after founding. Construction, manufacturing, and information technology companies have higher chances of survival compared to retail or wholesale businesses, transport companies and restaurants where more than 40 percent of firms have exited the market after five years (Brüderl, et. al., 1992). Young businesses have a higher risk of failure than older organizations. Some literature suggests that survival chances are higher for new food and beverage outlets on a franchise system or a system with a stable affiliation to an existing firm, as compared to independently set up outlets. The industry as a whole continually face demanding market and environment changes that requires business owners to actively manage these changes for survival, growth and ultimately sustainability. Restaurant businesses are still plagued with continual high employee attrition rate, decreasing consumer confidence and increasing government regulations that impacts sales and performance. Whilst some restaurant owners focus their attention on selected industry best practices, most attempt to combine three to four of such key success factors within a single framework in the areas of marketing, strategy, operations and human resources. Most entrepreneurs find this challenging due to limited resources and constant ‘fire-fighting’1 situations. This research papers thus aims to explore what some of these key success factors are through the use of literature and case studies, to help entrepreneurs and companies discover the attributes needed to possess in order to survive and succeed in the F&B business in the long term.